Characteristics of coastal aquifer contamination by seawater intrusion and anthropogenic activities in the coastal areas of the Bohai Sea, eastern China. (1st September 2021) - Xu, Xingyong; Xiong, Guiyao; Chen, Guangquan; Fu, Tengfei; Yu, Hongjun; Wu, Jichun; Liu, Wenquan; Su, Qiao; Wang, Yancheng; Liu, Shengfa; Shi, Xuefa
Graphical abstract: Highlights: 60, 000 km 2 of coastal aquifers are affected by seawater (saltwater) intrusion around Bohai Gulf. Palaeo-saltwater intrusion strongly affected groundwater evolution in Bohai Bay and Laizhou Bay. The seawater intrusion caused the enrichment of fluorine in coastal aquifers. Nitrate pollution increased in the coastal areas is a consequence of anthropogenic activities. Abstract: A comprehensive study was performed to identify the origins of salinity and the geochemical processes governing hydrochemistry, and to distinguish the role of evaporation, mixing, and water–rock interaction from seawater intrusion (SWI) or palaeo-saltwater intrusion (PSWI) on groundwater chemistry in the coastal aquifer around the Bohai sea in China. For these purpose, geochemical and multivariate statistical methods were applied. The results indicated that the intrusion area around the Bohai sea can be divided into: (i) the palaeo-saltwater intrusion zone (including the south of Laizhou Bay, Tianjin, and Panjin on the north of Liaodong Bay), and (ii) the modern seawater intrusion zone. The analysis of selected ions (Na + /Cl − and Br − /Cl − ) and isotopic compositions showed that the saltwater intrusion is the predominant factor of increasing salinity in groundwater, followed by water–rock interaction (e.g. mineral weathering and ion exchange), and evaporation. Sources of specific ions (Ca and F) are dominated by mineral weathering-dissolution rather than the saltwater intrusion. Furthermore, anthropogenic activities are the dominant cause of groundwater nitrate pollution in the coastal area around Bohai sea. This type of pollution is most serious in Liaodong Bay due to the industrial waste, fertilizers, pesticides, and domestic sewage. It is followed by pollution in Qinhuangdao due to agricultural and domestic factors, and pollution in Laizhou Bay due to domestic sewage. The source of high fluorine in groundwater is the dissolution of fluorine-containing minerals caused by saltwater intrusion. The degree of groundwater fluorine pollution is as follows: Liaodong Bay < Tianjin < Qinhuangdao < Laizhou Bay.